Assessing underlying pulsatile structures with laparoscopic tools using proximal vibroacoustic sensing - Kaabachi Syrine; Illanes Alfredo; Esmaeili Nazila; Sühn Thomas; Spiller Moritz; Friebe Michael; Hansen Christian; Boese Axel (Current Directions in Biomedical Engineering, 2024)
This work presents a novel approach for detecting underlying pulsatile structures with laparoscopic tools by using proximal vibroacoustic sensing. This new method could detect pulsations at a depth of up to 1.5 cm. The outcome of this work indicates the potential of identifying deep-seated pulsatile structures during robot-assisted laparoscopy, where haptic feedback is highly limited, to help surgeons prevent vascular damage that may lead to injuries.